Median nail dystrophy involving the thumb nail - Rahulkrishna Kota; Abhishek Pilani; Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2016)
Median canaliform dystrophy of Heller is a rare entity characterized by a midline or a paramedian ridge or split and canal formation in nail plate of one or both the thumb nails. It is an acquired condition resulting from a temporary defect in the matrix that interferes with nail formation. Habitual picking of the nail base may be responsible for some cases. Histopathology classically shows parakeratosis, accumulation of melanin within and between the nail bed keratinocytes. Treatment of median nail dystrophy includes injectable triamcinalone acetonide, topical 0.1% tacrolimus, and tazarotene 0.05%, which is many a times challenging for a dermatologist. Psychiatric opinion should be taken when associated with the depressive, obsessive-compulsive, or impulse-control disorder. We report a case of 19-year-old male diagnosed as median nail dystrophy.